IMPLIKASI SEJARAH HUKUM BAGI PEMBENTUKAN SISTEM HUKUM DI MASA DEPAN - Citra Irwan Simbolon; Baginda Rizky Ariesvy Sitanggang; Rosmalinda Rosmalinda (JOURNAL SAINS STUDENT RESEARCH, 2024)
Etymologically, the term “law” (recht) originates from the Latin rectum, or also referred to as ius, meaning to regulate or command. This indicates that human life in society is inseparable from conflict, as reflected in the phrase “Ubi societas ibi ius”, which means Where there is society, there is law. Every historical legal event in Indonesia, from the development of law during the pre-colonial era, Dutch colonization, Japanese occupation, independence, to modern legal reforms, has shaped the legal system adopted by Indonesia today. Therefore, it is crucial to design a legal system that is more adaptive and responsive to the evolving challenges of the times. This research discusses the implications of legal history for the formation of future legal systems and explores how legal history can influence the development of Indonesia's legal framework in the future.The research method used is normative juridical (legal research), analyzing legal regulations, theories, and concepts related to the issues under investigation.The research results indicate that an understanding of legal history provides deeper insight into how laws are created, modified, and enforced. During the Dutch colonial period, the Indonesian legal system began to be influenced by Western law. The legal system in Indonesia is a blend of European law, religious law, and customary law. The majority of the adopted systems, both civil and criminal, are based on the Continental European legal system. Legal history not only offers insight into the evolution of law but also serves as a guide to avoid past mistakes and to build a more responsive, inclusive, and just legal system for all Indonesian citizens. It is recommended that legal education place greater emphasis on legal history, and the Indonesian legal system must quickly adapt to emerging issues such as digital privacy, artificial intelligence, and international agreements.